Micropropagation of handroanthus heptaphyllus (Vell.) mattos from seedling explants - Duarte, Evelyn Raquel (2016)
Fil: Duarte, Evelyn Raquel. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.